(untitled) (Economic and Political Thought, 2023)
“A Political Science Analysis of Health Policy Theory” is an article that explores various health policy theories and their relevance to public health decision-making processes. The article highlights a variety of theories, such as interest theory, institutional theory, agenda-setting theory, political systems theory, and power and conflict theory, and examines how each of these theories helps to understand health policy. The authors of the article emphasize the role of pressure groups and social organizations in shaping health policy, as well as the influence of institutional structures on decision-making processes.